Pengaruh Latihan Plyometric terhadap Peningkatan Daya Ledak Otot Tungkai pada Atlet Taekwondo - Ahad Agafian Dhuha; Muhammad Muhibbi; Andre Yogaswara; Sayid Fariz Bin Seh Abubakar; Agung Widodo (Universitas Negeri Semarang, 2024)
The purpose of this study was to increase the explosive power of leg muscles in taekwondo athletes because in the match requires good explosive power to be able to kick hard and fast so as to produce points and win. The research method used was a quasi-experiment, with a vertical jump research instrument to measure explosive power, the research design used in this study was one group pre-test and post-test. The population in this study were 20 taekwondo athletes from the new temple dojang in Semarang city, the sampling technique used was total sampling. The results in this study average pre-test vertical jump was 28.8 cm, after being given plyometric squat jump training for 16 times of training then a post-test was carried out with an average post-test vertical jump result of 33.7 cm. so that after being given plyometric squat jump training the average increased by 4.9 cm or in a percentage of 33%. The conclusion in this study is that there is a significant effect of plyometric squat jump training on increasing explosive power of leg muscles, so this training method can be used as a reference in training explosive power of leg muscles.